2017
DOI: 10.1007/978-3-319-22801-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Very Young Massive Clusters and Implications for Globular Clusters

Abstract: How Very Young Massive star Clusters (VYMCs; also known as "starburst" clusters), which typically are of 10 4 M and are a few Myr old, form out of Giant Molecular Clouds is still largely an open question. Increasingly detailed observations of young star clusters and star-forming molecular clouds and computational studies provide clues about their formation scenarios and the underlying physical processes involved. This chapter is focused on reviewing the decadelong studies that attempt to computationally reprod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 140 publications
(95 reference statements)
1
10
0
Order By: Relevance
“…In particular, residual gas expulsion could lead to significant cluster expansion at early times, attenuating the long-term dynamical processing of BHs and thus altering the structural features of the clusters at late times. However, several recent analyses (e.g., Brinkmann et al 2017;Banerjee & Kroupa 2018) have shown that the early stages of formation of some clusters may feature a substantially more compact embedded phase of sub-pc length scale, comparable to the thickest molecular-cloud filaments, from which a substantial gas dispersal would result in sizes comparable to those of the initial configurations considered here and also of the observed gas-free young massive clusters, as demonstrated in Figure 1. While such processes may be important, they are beyond the scope of this analysis.…”
Section: Conclusion and Discussionsupporting
confidence: 48%
“…In particular, residual gas expulsion could lead to significant cluster expansion at early times, attenuating the long-term dynamical processing of BHs and thus altering the structural features of the clusters at late times. However, several recent analyses (e.g., Brinkmann et al 2017;Banerjee & Kroupa 2018) have shown that the early stages of formation of some clusters may feature a substantially more compact embedded phase of sub-pc length scale, comparable to the thickest molecular-cloud filaments, from which a substantial gas dispersal would result in sizes comparable to those of the initial configurations considered here and also of the observed gas-free young massive clusters, as demonstrated in Figure 1. While such processes may be important, they are beyond the scope of this analysis.…”
Section: Conclusion and Discussionsupporting
confidence: 48%
“…3.1). It is clear that with increasingly improved constraints on (differential) compact-binary merger rate density from LVK observations, it would be possible to provide constraints on widely debated issues regarding star cluster formation and large scale structure formation, e.g., mass dependence of cluster formation efficiency, R mort (M cl ), and lower and upper mass limits, [M GC,low , M GC,high ], of GC progenitors (see, e.g., Rodriguez et al 2015;Banerjee & Kroupa 2018;Kruijssen et al 2019;El-Badry et al 2019;Krumholz et al 2019). The differential merger rate density profiles would also help constraining the relative contributions of the various other channels for producing compact binary mergers, e.g., dynamical evolution of field hierarchical systems, mergers via Kozai-Lidov mechanism in galactic nuclei, and evolution of field massive binaries.…”
Section: Discussion: Uncertainties In Merger Rate Densitymentioning
confidence: 99%
“…In contrast, there is evidence for monolithic collapse in the formation of some young Galactic star clusters (e.g. Banerjee & Kroupa 2014, 2015, 2018).…”
Section: Imf Measurement Approaches: Neutral and Molecular Gas And Dustmentioning
confidence: 99%